SIKAP MASYARAKAT TERHADAP PROGRAM PEMBANGUNAN WILAYAH PESISIR DAERAH (KASUS IMPLEMENTASI PROGRAM TAMAN PESISIR KEPULAUAN DERAWAN DI KAMPUNG TANJUNG BATU KABUPATEN BERAU) - Yuda Prawijaya; Qoriah Saleha; Erwan Sulistianto (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The purpose of this study was to determine the socio-economic characteristics, perception, motivation, and public attitudes towards regional coastal development program. Also to know the relationship between socioeconomic characteristic, perception and motivation with public attitudes towards Derawan Island Coastal Park program. Sampling method use purposive sampling with 60 respondents, consist to 30 respondents of JALA and 30 respondents of Non JALA. The research has been conducted on July to December 2015. Data analysis methods use descriptive qualitative method and quantitative analysis method with Rank Spearman’s correlation. The result shows there is a difference in attitudes towards between JALA and Non JALA. The socioeconomic characteristics factors related with attitudes towards of Derawan Regional Coastal Park are membership status of JALA and ownership status of fishing gear. The perception and motivation factor has significant effect relationship toward public attitude of Tanjung Batu village toward of Derawan Islands Coastal Park.